2023
DOI: 10.1039/d3gc01756g
|View full text |Cite
|
Sign up to set email alerts
|

Alternative method to Baeyer–Villiger oxidation of cyclobutenones using I2/DMSO catalytic systems

Yichen Sun,
Zhibin Hu,
Jing Peng
et al.

Abstract: A novel and efficient approach utilizing I2/DMSO catalytic systems for the Baeyer–Villiger oxidative rearrangement of cyclobutenones was developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 71 publications
1
3
0
Order By: Relevance
“…It is reported that the interaction between halogen reagents and dimethyl sulfoxide (DMSO) could improve the halogenation and oxidative potential. 24 As expected, the DCE/DMSO combo (v : v = 1 : 1) remarkably increased the yield of 3aa to 75%, product 4aa via the imine hydrolysis pathway was totally inhibited (entry 7). The 10 : 1 ratio of DCE/DMSO (calculated 1.3 mmol DMSO in the reaction) further improved the yield of 3aa to 85% (entry 8).…”
Section: Resultssupporting
confidence: 63%
“…It is reported that the interaction between halogen reagents and dimethyl sulfoxide (DMSO) could improve the halogenation and oxidative potential. 24 As expected, the DCE/DMSO combo (v : v = 1 : 1) remarkably increased the yield of 3aa to 75%, product 4aa via the imine hydrolysis pathway was totally inhibited (entry 7). The 10 : 1 ratio of DCE/DMSO (calculated 1.3 mmol DMSO in the reaction) further improved the yield of 3aa to 85% (entry 8).…”
Section: Resultssupporting
confidence: 63%
“…Fine organic synthesis often involves intricate techniques and reagents. 1–3 Isolating essential substances and biologically active components can be challenging, especially when dealing with toxic and highly reactive reactants. 4–7 Modern researchers frequently face significant health risks in the laboratory setting.…”
Section: Introductionmentioning
confidence: 99%
“…DMSO, as a commonly used green solvent, also serves as an oxidizing agent in many reactions . Some of the classic examples include Swern oxidation, Kornblum oxidation, and Parikh–Doering oxidation .…”
mentioning
confidence: 99%